Image enhancement and unified segmentation approach in motion-blurred image for iris recognition [electronic resource] - D'yia Sarah Md. Shukri, 1988- (2013)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2013